2020
DOI: 10.1021/acs.jproteome.0c00519
|View full text |Cite|
|
Sign up to set email alerts
|

Integrative Modeling of Quantitative Plasma Lipoprotein, Metabolic, and Amino Acid Data Reveals a Multiorgan Pathological Signature of SARS-CoV-2 Infection

Abstract: The metabolic effects of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection on human blood plasma were characterized using multiplatform metabolic phenotyping with nuclear magnetic resonance (NMR) spectroscopy and liquid chromatography–mass spectrometry (LC-MS). Quantitative measurements of lipoprotein subfractions, α-1-acid glycoprotein, glucose, and biogenic amines were made on samples from symptomatic coronavirus disease 19 (COVID-19) patients who had tested positive for the SARS-CoV-2 v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

41
251
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 163 publications
(293 citation statements)
references
References 67 publications
41
251
1
Order By: Relevance
“… 6 We have shown that SARS-CoV-2 infection induces a metabolic “phenoconversion” process that gives a characteristic complex blood plasma signature exhibiting multiple pathological effects of the disease and in a complex mosaic of biochemical change. 7 This COVID-19 phenoconversion signature is readily detectable by both nuclear magnetic resonance (NMR) and mass spectrometric techniques, with the spectral profiles providing multiple windows onto the disease sequelae in different organ systems. 7 The general term, phenoconversion, is defined here as follows: “The systemic shift in multiple molecular phenotypic properties from the healthy to a characteristic activated or pathophysiological state in response to an infectious or a pathophysiological challenge”.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“… 6 We have shown that SARS-CoV-2 infection induces a metabolic “phenoconversion” process that gives a characteristic complex blood plasma signature exhibiting multiple pathological effects of the disease and in a complex mosaic of biochemical change. 7 This COVID-19 phenoconversion signature is readily detectable by both nuclear magnetic resonance (NMR) and mass spectrometric techniques, with the spectral profiles providing multiple windows onto the disease sequelae in different organ systems. 7 The general term, phenoconversion, is defined here as follows: “The systemic shift in multiple molecular phenotypic properties from the healthy to a characteristic activated or pathophysiological state in response to an infectious or a pathophysiological challenge”.…”
Section: Introductionmentioning
confidence: 99%
“… 7 This COVID-19 phenoconversion signature is readily detectable by both nuclear magnetic resonance (NMR) and mass spectrometric techniques, with the spectral profiles providing multiple windows onto the disease sequelae in different organ systems. 7 The general term, phenoconversion, is defined here as follows: “The systemic shift in multiple molecular phenotypic properties from the healthy to a characteristic activated or pathophysiological state in response to an infectious or a pathophysiological challenge”. The term has previously been used to describe accurately, but more narrowly, the process of cellular metabolic activation by drugs to alter the biochemical response to subsequent drug treatments via enzyme induction.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, although SARS-CoV-2 primarily targets the respiratory tract and lung, an increasing body of work has shown the virus to infect other organs like the gastrointestinal tract, liver, kidney, cardiac muscles, central nervous system, musculoskeletal system, and even reproductive system in males. 6,7 The diagnosis of the disease has been accurate and widespread. This was possible due to increased availability and deployment of RT-PCR assays, 8 or serological test kits, and scaling up of testing rates globally.…”
Section: Introductionmentioning
confidence: 99%